Case Report: Ultrasound-guided thrombin injection for the treatment of radial artery pseudoaneurysm after percutaneous coronary intervention - Li, Xiaoyan; Qi, Guoqing; Wei, Liye (Frontiers in Cardiovascular Medicine, 2026)
BackgroundRadial artery pseudoaneurysm (RAP) is an uncommon but significant complication after transradial coronary procedures. This case demonstrates the efficacy of ultrasound-guided thrombin injection (UGTI) as a minimally invasive treatment.Case presentationA 65-year-old Chinese male developed a RAP two days after percutaneous coronary intervention. Diagnosis was confirmed by Doppler ultrasound. UGTI was performed, injecting 1.5 mL of thrombin. Complete thrombosis occurred within 30 s, with sustained occlusion confirmed at 24-hour follow-up.ConclusionsUGTI is a highly effective and safe first-line treatment for iatrogenic RAP, enabling rapid resolution and avoiding the need for surgery. It represents a superior minimally invasive strategy for managing this vascular complication.